Menentukan Pengendalian dan Persediaan Bahan Baku Produksi UKM Keripik Murni Melalui Metode ReOrder Point - Andri Herlambang; Nita Marikena (Pusat Riset dan Inovasi Nasional, 2025)
Increased consumer demand has an influence on production results. Pure chips SMEs have obstacles in meeting their needs for raw materials such as sweet potatoes and cooking oil. The main raw materials are obtained from sweet potato farmers and cooking oil producers. Accurate and maximum calculation of raw materials is needed so that SMEs do not have problems in facing shortages or excesses of main raw materials. This research aims to assist pure chips SMEs in managing the amount of inventory of core raw materials to be produced into snacks. Research on the production of sweet potato and cooking oil supplies was carried out using a quantitative descriptive approach. The data obtained comes from pure chips UKM. Then the data will be analyzed using the reorder point method. From the calculation results, it was found that pure chips SMEs had to re-order sweet potato raw materials of around 8 kilograms per day and 3 liters of cooking oil raw materials per day.